addicted.pregnant.poor (Medicine Anthropology Theory, 2016)
addicted.pregnant.poor is an ethnography addressing the biomedical, social, political, and ethical dimensions of ongoing illicit drug use during pregnancy. A result of four years of fieldwork in daily-rent hotels – privately owned buildings in which the exploitation of women’s sex work and on-going poor health was normative – the book follows nineteen women who had twenty-three pregnancies. To answer the question ‘What forms of life are possible here?’ I engaged with the social actors who are called upon to produce knowledge about addicted pregnancy, including addicted, pregnant women; an anthropologist; public health epidemiologists; advocates; social policymakers; treatment professionals; bureaucrats; and scientists. In this essay, I describe the relationship between the scientific contours of reproductive health and the personal and social consequences of pregnancy in the context of addiction and housing instability. Pregnant women in the daily-rent hotels existed within multiple temporalities. Here I explore what an ethnographic understanding of memorial time and biomedical time can teach us about the vital politics of viability at work in addicted pregnancy.